Understanding change of direction ability in sport: A review of resistance training studies - Brughelli, M.; Cronin, J.; Levin, G.; Chaouachi, A. (Sports Medicine, 2008)
The ability to change direction while sprinting is considered essential for successful participation in most team and individual sports. It has traditionally been thought that strength and power development would enhance change of direction (COD) performance. The most common approach to quantifying these relationships, and to discovering determinants (physiological and mechanical) of COD performance, is with correlation analysis. There have not been any strength or power variables that significantly correlated with COD performance on a consistent basis and the magnitude of the correlations were, for the most part, small to moderate. The training studies in the literature that have utilized traditional strength and power training programmes, which involved exercises being performed bilaterally in the vertical direction (e.g. Olympic-style lifts, squats, deadlifts, plyometrics, vertical jumping), have mostly failed to elicit improvements in COD performance. Conversely, the training protocols reporting improvements in COD performance have utilized exercises that more closely mimic the demands of a COD, which include horizontal jump training (unilateral and bilateral), lateral jump training (unilateral and bilateral), loaded vertical jump training, sport-specific COD training and general COD training.